The entrepreneur's guide to risk and decisions : building successful early-stage ventures - Pittz, Thomas G.; Liguori, Eric (Emerald Publishing Limited, 2020)
Becoming a successful entrepreneur is impossible without accepting risk - the question is which risk to take and at what time. This guide offers practical, no-nonsense advice for marketing and financing your business, bringing on partners and employees, and launching your business as inexpensively and aggressively as possible.